Hybrid Electronics: Highly Robust Indium‐Free Transparent Conductive Electrodes Based on Composites of Silver Nanowires and Conductive Metal Oxides (Adv. Funct. Mater. 12/2014). (March 2014) - Zilberberg, Kirill; Gasse, Felix; Pagui, Richie; Polywka, Andreas; Behrendt, Andreas; Trost, Sara; Heiderhoff, Ralf; Görrn, Patrick; Riedl, Thomas
<x xml:space="preserve">Abstract</x> To overcome the limits of indium‐based transparent conductive materials, transparent conductive layers based on a composite of silver nanowires embedded in a conductive metal‐oxide are a promising alternative presented on page 1671 by T. Riedl and co‐workers. The metal‐oxide conductively joins the wires at their junctions and also 'glues' them to the substrate. A record‐low sheet resistance down to 5.2 Ohm/sq. is achieved with a concomitant average transmission of 87% for a composite prepared at room‐temperature. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>